Gambaran Gangguan Muskoloskeletal pada Perawat - Zifriyanthi Minanda Putri; Ilfa Khairina; Randy Refnandes (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Most of the health workers are nursing staff, nursing profession demands high physical activity ranks second after industrial workers. Musculoskeletal disorders often occur in health workers, nurses have a higher risk of experiencing the disorder. Musculoskeletal disorders are disorders that occur in the muscles, bones, tendons, blood vessels, nervous system, and other soft tissues. The purpose of this study was to determine the picture of musculoskeletal disorders in nurses in General Hospital. Dr. M. Djamil Padang. Research Methods: The method used in this research is descriptive. The number of samples in this study were 132 people. The sample selection in this study was the proportional random sampling method. The results showed that more than half (81.1%) nurses experienced musculoskeletal disorders. Musculoskeletal disorders complained of body parts: shoulders 49.2%, neck and lower back 41.7%, and upper back 32.6%. It is expected that nurses can identify the incidence of musculoskeletal disorders due to work and immediately report to management for further prevention.